2008
DOI: 10.1590/s1517-83822008000300031
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus infection in women attended at a cervical cancer screening service in Natal, Brazil

Abstract: We analyzed cervical specimens of 202 women, aged 15 to 64 years, attended at Luis Antonio Hospital, Natal, Brazil, to determine the prevalence of HPV and identify the more frequent genotypes and risk factors for HPV infection in women attended at a cervical cancer screening service. Two specimens were collected from each patient: one for cytological examination and the other to detect HPV DNA by PCR, and typing by dot blot hybridization. A total of 54.5% of the sample had normal cytology and 45.5% had cytolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 25 publications
4
9
0
5
Order By: Relevance
“…Concurrent infection with more than one HPV genotype was found in 10.8% of the analyzed population. This value is in the range observed for multiple infections among different studies (4,8,12,20,22).…”
Section: Cervical Lesions and Clinical Variablessupporting
confidence: 66%
“…Concurrent infection with more than one HPV genotype was found in 10.8% of the analyzed population. This value is in the range observed for multiple infections among different studies (4,8,12,20,22).…”
Section: Cervical Lesions and Clinical Variablessupporting
confidence: 66%
“…Os estudos no Brasil 15,16 apontam para a maior prevalência do HPV 58, principalmente na região Nordeste do país 10 . Porém, no presente estudo, o HPV 58 foi o oitavo genótipo mais comum.…”
Section: Discussionunclassified
“…Os achados cito-histopatológicos foram classificados em grupos de: achados negativos para neoplasia (exames citopatológico e histopatológico negativos), lesão de baixo grau (achado citopatológico -lesão intraepitelial de baixo grau -ou achado histopatológico -neoplasia intraepitelial cervical grau 1, neoplasia intraepitelial vaginal grau 1 ou condiloma e lesão de alto grau (achado citopatológico -lesão intraepitelial de alto grau -ou histopatologia com laudo maior ou igual a neoplasia intraepitelial cervical grau 2 ou neoplasia intraepitelial vaginal grau 2). RESULTADOS: O genótipo de alto risco mais frequente foi o HPV 16, com 18,5%; intervalo de confiança de 95% (IC95%) 14,6-23,0, seguido pelo HPV 56 (14%; IC95% 10,5-18,0) e o HPV 39 (13,4%; IC95% 9,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)8). O HPV 18 (5,4%; IC95% 3,3-8,3) esteve entre os menos comuns.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The worldwide prevalence in women with normal cytology is approximately 10% (de Sanjosé et al, 2007), whereas in women with abnormal cytology it is approximately 35% (Molijn et al, 2005). Studies conducted in several cities and states revealed a prevalence of HPV infection between 24.8 and 35.0% in Brazil (Nonnenmacher et al, 2002;Fernandes et al, 2008;Krambeck et al, 2008;Lippmann et al, 2010;Oliveira et al, 2010).…”
Section: Introductionmentioning
confidence: 99%